Pemanfaatan Tumbuhan Pangan Tradisional untuk Immunonutrient - Slamet Ifandi; Mita Dewi Retnoninggrum; Irmatul Laili (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2021)
This study aims to examine the knowledge of the community in Tiremenggal Village in utilizing food plants for immunonutrients. The research method used consists of two stages: the first stage of inventorying the level of community knowledge with exploratory survey methods and participatory ethnobotanical assessment through in-depth interviews (deep interviews) and structured (open-ended). The second stage is collecting data on the use of food plants using semi-structured interviews. The results showed that people's knowledge about food plants was obtained from asking other people (26%). The types of food plants identified were as many as 30 species covering staple food and additional food categories. In conclusion, the community's knowledge and ability in Tiremenggal village to utilize, compose and process traditional food plants as a source of immunonutrientts can be seen from the description of the aspects of their activities and activities. Keywords: Tiremenggal Village, Immunonutrients, Food Plants